EVALUASI PELAKSANAAN PPLK1 DI UNBAJA - Haryati Haryati; Budi Mulyati (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
Learning Process of PPLK 1 or micro teaching was a Learning Process that learn about the practice of teaching for students that involves their classmates who became learners in the learning process. The purpose of this research were : 1) to know how to prepare PPLK 1 in UNBAJA, 2) to know how was learning process of PPLK 1 in UNBAJA, 3) to know how was the facility for PPLK 1 in UNBAJA. This research used qualitative approach method. The object of research were the dean of FKIP, lecturer of PPLK 1 and the students of Accounting Education Program on semester 6. In this research the data collection techniques were interview, observation and documentation. Data analysis in this research used descriptive qualitative. The results showed that thelearning process of PPLK 1 at the University of Banten Jaya has been running well, student learning process could perform in front class confidently and they could teach like as a teacher. However, the learning process still need improvements, especially in time management and procurement of infrastructure facilities to support the PPLK 1